Atypical presentation of necrotising autoimmune myopathy. Issue 5 (28th May 2019) - Ajiboye, Oyintayo; Manesh, Michelle; Asmi, Nisar; Mba, Benjamin
Abstract : Necrotising autoimmune myopathy (NAM) is characterised by a common phenotype of profound symmetrical proximal muscle weakness, elevated creatine kinase levels, irritable myopathy on electromyography and histological findings of myocyte necrosis and regeneration without remarkable inflammation. NAM is associated with autoimmune antibodies including anti-3-hydroxy-3-methylglutaryl-coenzyme receptor, which is strongly associated with statin use. We report a case of statin-associated NAM with an atypical presentation of severe oropharyngeal dysphagia and no remarkable proximal muscle weakness at initial presentation but with rapid progression to severe quadriparesis in weeks. This case expands the spectrum of presentation patterns of this rare disease and highlights the need for a high index of suspicion in patients with a remote history of statin use.